Breast cancer patients' most important quality of life themes for a radiotherapy decision aid. (October 2022) - Roumen, Cheryl; Hasannejadasl, Hajar; Swart, Rachelle; Raphael, Daniela; Wee, Leonard; Sloep, Matthijs; van den Bongard, Desiree H.J.G.; Verkooijen, Helena; Thijssen, Salina; Velting, Mirjam; Schuurman, Maaike; Russell, Nicola S.; et al.
Abstract: Background and aim: The BRASA patient decision aid (BRASA-PtDA) facilitates shared decision making for breast cancer patients (BCPs) facing a radiotherapy treatment decision. During evaluations, patients indicated the wish for quantitative information on side effects. Therefore, this study assessed BCPs opinion on which and how information on side effects should be incorporated in the BRASA-PtDA. Methods: A workshop was organized with BCPs (n = 9), researchers (n = 5) and clinicians (n = 3). Subsequently, a survey was sent to BCPs (n = 744) investigating the generalisability of the workshop findings, and posing additional questions. The survey entailed multiple choice questions on quality of life themes, the use of a decision aid and risk communication. Results: The workshop revealed BCPs wish for a layered, all encompassing information system. Information on the impact of side effects on daily life was preferred above the risk of these side effects. The survey revealed that important quality of life (QoL) themes were having energy (81%; n = 605), arm function (61%; n = 452), pain (55%; n = 410). Despite the focus on qualitative effects in the workshop, 89% of the survey respondents also wanted to be informed on individualized risks of side effects. 54% Of the survey respondents had never heard of a PtDA. Conclusions: BCPs preferred information on the impact of side effects, but also their individualized risks on side effects. Most important QoL themes were having enough energy, arm function and pain. Consequently, the BRASA-PtDA should be reshaped, starting with quality of life themes, rather than side effects. Highlights: Having enough energy is the most important QoL theme for patients. The practical impact of side effects on daily life are more important than personal risks. Half of the former patients did not know what a decision aid was. Patients stress the importance of a layered information system.